Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s40813-020-0145-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of alternative measures to reduce antimicrobial usage in pig production in four European countries

Abstract: Background The reduction of antimicrobial usage (AMU) is in the focus in modern pig production. The objective of this study was to assess the effectiveness of alternatives to reduce AMU at herd level. In a prospective study, 68 farrow-to-finish pig herds located in Belgium, France, Germany and Sweden were recruited on a voluntary basis to implement tailor-made intervention plans to reduce their AMU. Alternative measures included improvement of biosecurity (n = 29 herds), vaccination (n = 30), changes of feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 30 publications
0
30
1
Order By: Relevance
“…These results may be explained by larger farms paying more attention to biosecurity and management. A positive relationship between farm size and biosecurity was described in a Belgian study [ 39 ] and higher or improved biosecurity may lead to lower AMU [ 30 , 39 , 40 , 41 , 42 ]. Therefore, factors that could influence AMU (e.g., management, biosecurity, housing system, alternatives to antimicrobials) should be further investigated in Italian pig farms.…”
Section: Discussionmentioning
confidence: 99%
“…These results may be explained by larger farms paying more attention to biosecurity and management. A positive relationship between farm size and biosecurity was described in a Belgian study [ 39 ] and higher or improved biosecurity may lead to lower AMU [ 30 , 39 , 40 , 41 , 42 ]. Therefore, factors that could influence AMU (e.g., management, biosecurity, housing system, alternatives to antimicrobials) should be further investigated in Italian pig farms.…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions will need to overcome the diversity of production systems and value chains they depend on and the patterns of AMU in these systems and their policy contexts. A number of interventions have already taken place in developed countries based on improvements in biosecurity and husbandry practices aiming at reducing AMU in pigs ( 19 21 ) and broilers ( 22 ). However, no intervention studies targetting AMU in small-scale farming systems from LMICs have been published.…”
Section: Introductionmentioning
confidence: 99%
“…A similar holistic approach was adopted on a study on pig farms in Belgium, resulting in 52% AMU reduction in pigs raised from birth to slaughter, and by 32% among breeding animals; furthermore, the study resulted in additional productivity gains (Postma et al, 2017). Similarly, a study conducted in four European Union (EU) countries reported AMU reductions of 3% and 54% in fattening in weaned pigs, respectively following improvements of herd management practices (Raasch et al, 2020). However, reductions in AMU were not seen in breeding pigs, and the authors attributed it to the concurrent incursion of Porcine Epidemic Diarrhoea (PED) in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions will need to overcome the diversity of production systems and value chains they depend on and the patterns of AMU in these systems and policy contexts. A number of interventions have already taken place in developed countries based on improvements in biosecurity and husbandry practices aiming at reducing AMU in pigs (Raasch et al, 2020;Postma et al, 2017;Rojo-Gimeno et al, 2016) and broilers (Roskam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%